Ribulose 1,5-Bisphosphate Carboxylase/Oxygenase Is Required in Bradyrhizobium diazoefficiens for Efficient Soybean Root Colonization and Competition for Nodulation - Rocío S. Balda; Carolina Cogo; Ornella Falduti; Florencia M. Bongiorno; Damián Brignoli; Tamara J. Sandobal; María Julia Althabegoiti; Aníbal R. Lodeiro (Plants, 2024)
The Hyphomicrobiales (Rhizobiales) order contains soil bacteria with an irregular distribution of the Calvin–Benson–Bassham cycle (CBB). Key enzymes in the CBB cycle are ribulose 1,5-bisphosphate carboxylase/oxygenase (RuBisCO), whose large and small subunits are encoded in cbbL and cbbS, and phosphoribulokinase (PRK), encoded by cbbP. These genes are often found in cbb operons, regulated by the LysR-type regulator CbbR. In Bradyrhizobium, pertaining to this order and bearing photosynthetic and non-photosynthetic species, the number of cbbL and cbbS copies varies, for example: zero in B. manausense, one in B. diazoefficiens, two in B. japonicum, and three in Bradyrhizobium sp. BTAi. Few studies addressed the role of CBB in Bradyrhizobium spp. symbiosis with leguminous plants. To investigate the horizontal transfer of the cbb operon among Hyphomicrobiales, we compared phylogenetic trees for concatenated cbbL-cbbP-cbbR and housekeeping genes (atpD-gyrB-recA-rpoB-rpoD). The distribution was consistent, indicating no horizontal transfer of the cbb operon in Hyphomicrobiales. We constructed a ΔcbbLS mutant in B. diazoefficiens, which lost most of the coding sequence of cbbL and has a frameshift creating a stop codon at the N-terminus of cbbS. This mutant nodulated normally but had reduced competitiveness for nodulation and long-term adhesion to soybean (Glycine max (L.) Merr.) roots, indicating a CBB requirement for colonizing soybean rhizosphere.